Inventarisasi Jenis-Jenis Tanaman Pekarangan Dan Pemanfaatannya Di RW 11 Kelurahan Kebonjayanti Kecamatan Kiaracondong Kota Bandung - Najmi Azalia Ubaedilah; Sri Ajeng Mulyani; Vutri Suci Fatimah; Ateng Supriatna (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
The yard of the house is an area of ​​land covered with various types of plants. Most of the plants in the house yard were deliberately planted by the owner. This research aims to manifest diversity and inventory types of garden plants in the homes of residents of RW 11, Kebonjayanti Village, Kiaracondong District, Bandung City. The research method used to obtain research data is an exploratory method. This research was carried out by exploring and observing directly the types of garden plants. Plants are identified using the help of the PlantNet application. Based on research data from the RW 11 area, Kebonjayanti Village, Kiaracondong District, Bandung City, 81 types of plants were found consisting of 40 families. The dominant family is the Araceae family.